Training on Simple Financial Reports for BUMDes in Bojonegara sub-District Serang Regency - Nurhayati Soleha; Agus Sholikhan Yulianto; Imam Abu Hanifah; Chandra Prasadhita; Tri Wahyudi (MOVE: Journal of Community Service and Engagement, 2023)
BUMDes financial reports are crucial because the reports involve in the use of economic resources that come from the community and/or the government. For this reason, training for BUMDes is needed regarding preparing financial reports according to accounting standards so that BUMDes accountability and transparency can be achieved. Through community service activity, BUMDes management understands the importance of preparing financial reports based on accounting standards (SAK), however, in practice, BUMDes have not been able to implement financial reports according to accounting standards yet.